Proceedings of the 57th Annual Meeting of the Association for Computational Linguistics: Student Research Workshop 2019
DOI: 10.18653/v1/p19-2010
|View full text |Cite
|
Sign up to set email alerts
|

Automated Cross-language Intelligibility Analysis of Parkinson’s Disease Patients Using Speech Recognition Technologies

Abstract: Speech deficits are common symptoms among Parkinson's Disease (PD) patients. The automatic assessment of speech signals is promising for the evaluation of the neurological state and the speech quality of the patients. Recently, progress has been made in applying machine learning and computational methods to automatically evaluate the speech of PD patients. In the present study, we plan to analyze the speech signals of PD patients and healthy control (HC) subjects in three different languages: German, Spanish, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Speech signals are usually considered as one of the main methods to diagnose Parkinson's disease. In [5] authors performed experimentation on speech signal recordings of three languages identifying speech pronunciation problems in it. It is observed that speech pronunciation like vowels, sentences, words are affected by this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Speech signals are usually considered as one of the main methods to diagnose Parkinson's disease. In [5] authors performed experimentation on speech signal recordings of three languages identifying speech pronunciation problems in it. It is observed that speech pronunciation like vowels, sentences, words are affected by this disease.…”
Section: Introductionmentioning
confidence: 99%
“…While motor tests such as tremor, gait and finger tapping are applicable regardless of the individual’s language, in the case of speech tests, the subject may be unable to understand the test or complete it successfully due to challenges with pronunciation, which may influence the test results and their interpretation ( 133 ). To overcome this, the voice tests used for Parkinson’s disease risk survey digital platform implemented in Thailand comprise newly developed speech tests that use sustained vowels (making a loud “Aah” sound for 10 s to assess phonation) and speaking sentences in Thai language (to assess prosody and articulation), thereby enhancing its relevance for Thai native speakers.…”
Section: Methods and Analysismentioning
confidence: 99%
“…With the constant disease progression, it turns to be another condition known as dementia. When an individual is influenced by PD possess risk of two-six times towards dementia when compared to other population [4].…”
Section: Introductionmentioning
confidence: 99%